2006
DOI: 10.1002/glia.20366
|View full text |Cite
|
Sign up to set email alerts
|

A dual tyrosine‐leucine motif mediates myelin protein P0 targeting in MDCK cells

Abstract: Differential targeting of myelin proteins to multiple, biochemically and functionally distinct Schwann cell plasma membrane domains is essential for myelin formation. In this study, we investigated whether the myelin protein P0 contains targeting signals using Madin-Darby canine kidney (MDCK) cells. By confocal microscopy, P0 was localized to MDCK cell basolateral membranes. C-terminal deletion resulted in apical accumulation, and stepwise deletions defined a 15-mer region that was required for basolateral tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 72 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…While T216ER behaved very similarly to wt-P0ct, its role in CMT etiology could be of another origin than related to protein-membrane binding. A221T, on the other hand, resides in the YAML-motif, which directs the trafficking of P0 (Kidd et al 2006) and might compromise the function of P0 even without inducing changes in membrane binding, especially when combined with a second mutation in the extracellular domain, such as the deletion of Val42 (Planté-Bordeneuve et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While T216ER behaved very similarly to wt-P0ct, its role in CMT etiology could be of another origin than related to protein-membrane binding. A221T, on the other hand, resides in the YAML-motif, which directs the trafficking of P0 (Kidd et al 2006) and might compromise the function of P0 even without inducing changes in membrane binding, especially when combined with a second mutation in the extracellular domain, such as the deletion of Val42 (Planté-Bordeneuve et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the known functions for P0 cytoplasmic domain, which is truncated in P0Q215X, is to target the protein to myelin (Kidd et al, 2006), we analysed in detail the membrane targeting of the protein, and found that Q215X was increasingly mis-directed to non-myelin plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
“…P0Q215X lacks a YAML sequence in its C-terminal region, which has previously been implicated in myelin membrane targeting (Kidd et al, 2006). In order to address whether this determines the altered trafficking of P0Q215X, we used an in vitro assay where the YAML motif directs P0 trafficking to the basolateral surface of transfected and polarized MDCK cells (Kidd et al, 2006).…”
Section: The Yaml Sequence In the Cytoplasmic Tail Regulates P0 Traffmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, both isoforms of MAG contain a sequence resembling a clathrin‐coated pit internalization signal, including a tyrosine, which is crucial for basolateral sorting (Matter and Mellman, 1994). Of further interest, in the myelin protein P 0 , a dual tyrosine‐leucine motif that mediates basolateral targeting in MDCK cells has been identified (Kidd et al, 2006). Finally, PLP contains a dileucine motif that localizes in the N‐terminal region immediately next to the palmitoylation sites, which were reported to be imperative for the proper transport of PLP to the myelin sheet (Pham‐Dinh et al, 1991; Schneider et al, 2005).…”
Section: Discussionmentioning
confidence: 99%